Odpowiedź :
Odpowiedź:
Zadanie wykonam w załączniku
Szczegółowe wyjaśnienie:
Odpowiedź i szczegółowe wyjaśnienie:
[tex]a)\ log_4\dfrac{\sqrt2}{2}=log_{2^2}\dfrac{2^\frac12}{2}=log_{2^2}2^{\frac12-1}=log_{2^2}2^{-\frac12}=-\frac12log_{2^2}2=\\\\=-\frac12\cdot\frac12log_22=-\frac14log_22=-\frac12\cdot1=-\frac14[/tex]
[tex]b)\ log_42\sqrt2=log_{2^2}2\cdot2^\frac12=log_{2^2}2^{1+\frac12}=log_{2^2}2^\frac32=\\\\=\dfrac32log_{2^2}2=\dfrac32\cdot\dfrac12log_22=\frac34log_22=\dfrac34\cdot1=\dfrac34[/tex]